Development of a Piezoceramic Harvester for Sea Waves Energy Recovery in Environmental Monitoring Buoys - Roberto Montanini; Antonio Cannuli; Fabrizio Freni; Antonino Quattrocchi; Andrea Venuto (Sensors)
In the last decades, marine environment monitoring has gained significant attention as it plays a fundamental role in ecosystem health and anthropogenic impact evaluation. This study presents the development of a sea wave energy recovery device based on piezoceramic harvesting, designed to contribute to the energy self-sufficiency of an environmental monitoring buoy. The system consists of a flexible S-shaped arm anchored to the buoy structure; the buoyancy system at the free end converts wave-induced motion into mechanical stress, deforming the opposite side of the arm, where piezoceramic patches are installed to generate electrical power. An extensive experimental campaign was conducted to perform the electromechanical characterization of the device and to analyze the manufacturing quality of the arm, produced by stereolithographic additive manufacturing. The results demonstrate the ability to harvest kinetic energy across a range of wave frequencies and amplitudes. Under the best conditions, a maximum transfer electric power of 220.2 ± 3.7 µW was reached.